Physico-chemical Properties of Gallstones - Nusier, Mohamad; Shawakfeh, Khaled; Otoom, Sameer (Asian Journal of Chemistry, 2012)
Gallstones found in the gallbladder are classified based on their chemical composition as cholesterol, mixed or pigmented stones. In the present study, the morphology and the chemical composition of gallstones obtained from patients with colelithiasis have been examined. The investigations were carried out using various chemical, spectroscopic and X-radiographic methods. The number of stones obtained from patients with colelithiasis ranged from 1 to 90 and the majority (75%) of these stones was cholesterol or mixed, while the rest (25%) were calcium carbonate, calcium bilirubinate or organic stones. The majority of cholesterol or mixed gallstones analyzed had a layer structure with patches of pigmented material. Multistones were small, spherical, and contained fibrous material at their centres. Furthermore, some of these stones were heavily pigmented at their centres. Some stones were long and black with irregular shape and were mainly composed of calcium bilirubinate and had no cholesterol. The majority of gallstones described and analyzed in the target group was cholesterol or mixed in composition. The remaining minority of gallstones was pigmented, which usually have less cholesterol than cholesterol or mixed gallstones.